Low-voltage electricity network monitoring system: Design and production experience - Aleksandar Stanimirović; Miloš Bogdanović; Milena Frtunić; Leonid Stoimenov (International Journal of Distributed Sensor Networks)
This article describes the low-voltage distribution network monitoring system developed for the Electric Power Industry of Serbia electricity distribution company. The implemented system is deployed in two different regional centers of the Electric Power Industry of Serbia and is being used in production for the past 4 years. During this period, it has collected real-life data which was used to analyze and investigate low-voltage distribution network performances as well as to identify and study energy losses in low-voltage distribution networks. The main contribution of this article is represented by the real-life monitoring and control infrastructure implementation insights. Furthermore, the system we describe in this article became a part of company’s enterprise information system, thus becoming integrated with heterogeneous information sources. This integration generated additional values to the company since the collected measurements started to improve the quality of the decision-making system for everyday business processes.